Impact Of Apologetic Responses On Guest Complaints For Creating Loyal Customer Base And The Art Of Restoring Repeat Business In Star Rated Hotels (International Journal of Food and Nutritional Sciences, 2022)
Many organisation have realised today that by Encouraging their guests for posting their views and experiences online, is helping them to respond positively it also helps to build the reputation of the organisation in a positive way. Currently apologizing helps the organisation in taking the responsibility for their actions, and getting rid of the self-esteem guilt. This study tries to gauge the power of apology for online reviews as well as Physical complaints in the hotels. For this research Interviewing Senior managers, guest visiting three to five- star category hotels the data was analysed through the application of statistical tool, collected data through primary source and conclusions based on the findings of the study were drawn.